Scanning Electron Microscopic Analysis of Clays in The Soils of Lower Atrai Basin of Bangladesh (Dhaka University Journal of Biological Sciences, 2022)
Scanning electron microscopic (SEM) analysis of clay samples from four different soil series, viz. Binsara, Taras, Jaonia, and Manda in the Lower Atrai Basin of Bangladesh was performed to characterize the clay minerals. The micrographs of SEM were obtained at three different magnification levels, such as low (2,000x), medium (5,000x), and high (10,000x). The SEM proved to be ideally feasible for studying the size, shape, texture, and fabric of clay samples. The electron micrographs of clays in the Binsara soil series have shown well-formed six-sided flakes. These six-sided flake particles are 1 : 1 type (well-crystallized) kaolinite minerals. The lath-shaped, rounded flakes are the well crystallized 2:1 type illite mineral in clays of Taras and Jaonia soil series. The rod-shaped fluffy masses/flakes are the indication of the presence of 2 : 1 type vermiculite in the clays of Manda soil series. The rounded particles in all soils are quartz grains.Dhaka Univ. J. Biol. Sci. 31(1): 105-115, 2022 (January)